Creating the Strategic and Technical Advisory Group of Experts (STAGE) to advance maternal, newborn, child, adolescent health and nutrition: A new approach - Strategic and Technical Advisory Group of Experts; Ruel, Marie T. (BMJ, 2021)
The Strategic and Technical Advisory Group of Experts (STAGE) for Maternal, Newborn, Child, Adolescent Health and Nutrition (MNCAHN) which advises the Director-General of WHO, marked its first anniversary in April 2021 as it concluded its third virtual meeting. STAGE has 31 members from all WHO regions and includes the key discipline groups that focus on MNCAHN. STAGE is an independent advisory group that takes a critical look at initiatives and programmes at WHO related to MNCHAN. STAGE provides an opportunity to monitor progress, connect agendas and groups and is a space to facilitate synergies across WHO departments, as well as with other United Nations (UN) agencies.